Stability analysis in rapeseed and mustard for resistance to Alternaria leaf blight and white rust - and C.D. KAUSHIK, LEKH RAJ, V.P. SINGH (Indian Phytopathology, 2002)
Fifty four genotypes of 4 Brassica spp. (B. juncea, B. campestris, B. carinata and B. napus) were evaluated for their disease interaction to Alternaria leaf blight (A. brassicae) and white rust (Albugo candida) during 1992-93 and 1993-94. Stability analysis was performed. G X E interaction for the traits was significant and predictable. Incidence of white rust was not recorded in B. campestris, B. carinata and B. napus. PCRS (susceptible to Alternaria leaf blight and white rust), PT303 and C6YS7B (moderately susceptible to Alternaria leaf blight) genotypes were stable for both traits. None of the genotypes of B. napus were stable to Alternaria leaf blight disease.